Use of Flame Atomic Absorption Spectrometry in Diagnosis of Cancerous and Non-Cancerous Breast Tissues: Comparison of Metal Concentrations - Kaya, Gokce; Akdeniz, Ismail; Ozcan, Cemile; Kilinc, Ersin; Yaman, Mehmet (Atomic Spectroscopy Press Ltd, 2010)
Metals play important roles for cellular functions and also for generating oxidative DNA damages. Furthermore, they are considered to act not only as carcinogens but also as co-carcinogens which activate carcinogenic chemicals. The question of whether trace metal concentrations in tissues increase or decrease in cancerous patients has not been answered with certainty, since the data in this area are both rare and include contrary results. This confusion can be attributed to differences in digestion methods of tissues and reliability of analysis techniques. In this study, concentrations of trace metals including Cd, Ni, Cu, Zn, Fe, Mg, and Ca in both cancerous and non-cancerous breast tissues were determined by flame atomic absorption spectrometry. The tissue samples were digested by using microwave energy. The average concentrations of Cu, Zn, Fe, Mg, and Ca were 0.7, 13, 22, 129 and 260 mu g/g, respectively) in cancerous women's breast tissues found to be significantly higher (p<0.05) than those in non-cancerous women's breast tissues (0.4, 7, 12, 55, and 165 mu g/g, respectively), for the paired samples. Thus, the concentration levels of these metals can be considered for diagnosis of cancerous and non-cancerous breast tissues.
Keywords: Trace-Element Concentrations; Dna-Damage; Synchrotron Xrf; Zinc Levels; Copper; Cadmium; Benign; Lead; Sensitivity; Calcium